John Lydgate’s Use of Prepositions and Adverbs Meaning ‘Between’ - Ciszek-Kiliszewska, Ewa (Studia Anglica Posnaniensia, 2016)
The most spectacular finding is that John Lydgate regularly uses atwēn, twēn(e) and atwix(t)(en), which are recorded in hardly any other Middle English texts. Moreover, the former two lexemes, and sporadically also atwix(t)(en), produce the highest number of tokens of all lexemes meaning ‘between’ in each analysed Lydgate’s text, which is unique in the whole history of the English language.